2021
DOI: 10.3389/fonc.2021.666014
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: ANXA2 Associated Life-Threatening Coagulopathy With Hyperfibrinolysis in a Patient With Non-APL Acute Myeloid Leukemia

Abstract: Patients with acute promyelocytic leukemia (APL) often present with potentially life-threatening hemorrhagic diathesis. The underlying pathomechanisms of APL-associated coagulopathy are complex. However, two pathways considered to be APL-specific had been identified: 1) annexin A2 (ANXA2)-associated hyperfibrinolysis and 2) podoplanin (PDPN)-mediated platelet activation and aggregation. In contrast, since disseminated intravascular coagulation (DIC) is far less frequent in patients with non-APL acute myeloid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 20 Other studies have reported increased tPA and uPA concentrations, 43 , 44 however, we found these parameters to be within the reference range. Annexin II was also associated with hyperfibrinolytic coagulopathy and bleeding diathesis in a recent case report of a patient with acute myelomonocytic leukemia (AMML), 45 and, moreover, Olwill et al found that annexin II was highly expressed in APL, AMML, and erythroid leukemia cell lines. 45 , 46 Several case reports spanning multiple decades have also associated AMML with disseminated intravascular coagulation and hyperfibrinolysis 47 , 48 , 49 Thus, annexin II–associated hyperfibrinolysis does not seem to be exclusive to APL.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Other studies have reported increased tPA and uPA concentrations, 43 , 44 however, we found these parameters to be within the reference range. Annexin II was also associated with hyperfibrinolytic coagulopathy and bleeding diathesis in a recent case report of a patient with acute myelomonocytic leukemia (AMML), 45 and, moreover, Olwill et al found that annexin II was highly expressed in APL, AMML, and erythroid leukemia cell lines. 45 , 46 Several case reports spanning multiple decades have also associated AMML with disseminated intravascular coagulation and hyperfibrinolysis 47 , 48 , 49 Thus, annexin II–associated hyperfibrinolysis does not seem to be exclusive to APL.…”
Section: Discussionmentioning
confidence: 99%
“…The CLEC-mediated platelet adhesion to PDPN is important in the development and dissociation of lymphatics from blood vessels, in supporting the integrity of the blood-lymphatic vessel junctions, in preventing blood cell efflux into lymphatics and in maintaining vascular integrity during inflammation [ 23 ]. There were reports that PDPN related to platelet aggregation and annexin A2 (ANXA2) related to hyperfibrinolysis were related to life-threatening coagulopathy in acute promyelocytic leukemia (APL) and non-APL, respectively [ 25 , 26 ]. The JAK-STAT pathway is involved in immune response, inflammation and tumorigenesis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%